Size‐Controllable Eu‐MOFs through Machine Learning Technology: Application for High Sensitive Ions and Small‐Molecular Identification. Issue 6 (22nd April 2022) - Zhang, Qi; Liang, Hanwei; Tao, Yangtianze; Yang, Jianxin; Tang, Bin; Li, Rui; Ma, Yun; Ji, linhong; Jiang, Xuan; Li, Shuangshou
Abstract: Metal‐organic frameworks (MOFs) with the aggregation‐induced emission (AIE) activities exhibit potential applications in the fields of energy and biomedical technology. However, the controllable synthesis of MOFs in the varied particle sizes not only affects their AIE activities, but also restricts their application scenarios. In this work, the varied particle sizes of Eu‐MOFs are synthesized by adjusting the synthesis process parameters, and their variation rules combining the single factor analysis method with machine learning technology are studied. Based on the R 2 score, the gradient boosting decision tree (GBDT) regression model (0.9535) is employed to calculate the weight and correlation between different synthesis process parameters and it is shown that all these parameters have synergic effects on the particle sizes of Eu‐MOFs, and the Eu‐precursors concentration dominates in their synthesis process. Furthermore, it is indicated that the large size of Eu‐MOFs and strong structural stability contribute to their high AIE activities. Finally, a screen‐printed pattern is fabricated using the sample of "120–0.3–6, " and this pattern exhibits a bright red fluorescence under the UV light. More importantly, this kind of Eu‐MOFs can also be used to identify varied ions (Fe 3+, F –, I –, SO4 2–, CO3 2–, and PO4 3– ) and citric acid. Abstract : The Eu‐MOFs are fabricated in the varied conditions, and their variation rule for controllable synthesis of the different sizes of Eu‐MOFs by combining single factor analysis with machine learning is explored.